2004
DOI: 10.1177/175899830400900303
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Complex Regional Pain Syndrome Type I on an Individual's Occupational Performance

Abstract: This research study examined the effect of Complex Regional Pain Syndrome (CRPS) Type I, on a person's occupational performance. Ten subjects with a diagnosis of CRPS Type I were investigated by using a semi-structured interview followed by two standardised assessments: the Canadian Occupational Performance Measure (COPM) and a Visual Analogue Scale (VAS). The COPM measured occupational performance, and the VAS measured pain intensity. Descriptive data on participants' views and their perspectives on responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…CRPS is estimated to affect up to 30% of persons following upper-extremity injuries or surgeries and may become chronic in about 2% (Albazaz, Wong, & Homer-Vanniasinkam, 2008; de Mos et al, 2009). Brincat (2004) used qualitative interviews to explore the impacts of upper-extremity CRPS on occupational performance. He reported that persons with CRPS experienced substantial loss of daily life roles and activities, with both psychological and economic repercussions (Brincat, 2004).…”
Section: Complex Regional Pain Syndrome (Crps)mentioning
confidence: 99%
See 1 more Smart Citation
“…CRPS is estimated to affect up to 30% of persons following upper-extremity injuries or surgeries and may become chronic in about 2% (Albazaz, Wong, & Homer-Vanniasinkam, 2008; de Mos et al, 2009). Brincat (2004) used qualitative interviews to explore the impacts of upper-extremity CRPS on occupational performance. He reported that persons with CRPS experienced substantial loss of daily life roles and activities, with both psychological and economic repercussions (Brincat, 2004).…”
Section: Complex Regional Pain Syndrome (Crps)mentioning
confidence: 99%
“…Brincat (2004) used qualitative interviews to explore the impacts of upper-extremity CRPS on occupational performance. He reported that persons with CRPS experienced substantial loss of daily life roles and activities, with both psychological and economic repercussions (Brincat, 2004).…”
Section: Complex Regional Pain Syndrome (Crps)mentioning
confidence: 99%